Knowledge of isolation precautions among the healthcare workers in the emergency department of a university hospital - Sertçelik, Ahmet; Arslan, Volkan; Karadogan, Eda; Uzar, Hanife; Cakir, Banu; Metan, Gokhan (Acta Medica, 2023)
Objectives: Prevention and control of healthcare-associated infections are important for patients and personal safety and for fighting against antimicrobial resistance. In order to achieve the goal of zero infection, it is necessary to know and apply standard and transmission-based precautions. The aim of this study was to evaluate the knowledge of healthcare professionals working in the Adult Emergency Department of university hospital about isolation precautions. Methods: A cross-sectional study was conducted in the Emergency Department of Hacettepe University Hospital between May 16, 2023 to June 23, 2023. Data were collected electronically with a standardized data collection form specially prepared for this study to examine the knowledge about isolation precautions. Each correct answer was calculated as one point. Participants could receive a score between a minimum of 0 and a maximum of 20. Results: The 90 healthcare workers who agreed to participate in the study had a median age of 24 years and 40% were male. The median knowledge score was 13 (IQR = 4). The knowledge score of two pregnant healthcare workers was significantly higher than non-pregnant ones (p=0.04). 93.3% of the participants stated that they received education for isolation precautions. There was no significant difference in knowledge scores between those who received education and those who did not (p=0.02). Knowledge of isolation precautions to be followed in clinical scenarios (1.1% - 54.4%) and personal protective equipment to be used correctly (3.3% - 21.1%) was low. Conclusion: The knowledge of healthcare professionals working in the Adult Emergency Department of university hospital about isolation precautions is at a moderate level. Periodical education programs on clinical scenarios is important regarding raising awareness.